2019
DOI: 10.1523/jneurosci.1106-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Imbalanced Corticospinal and Reticulospinal Contributions to Spasticity in Humans with Spinal Cord Injury

Abstract: Damage to the corticospinal and reticulospinal tract has been associated with spasticity in humans with upper motor neuron lesions. We hypothesized that these descending motor pathways distinctly contribute to the control of a spastic muscle in humans with incomplete spinal cord injury (SCI). To test this hypothesis, we examined motor-evoked potentials (MEPs) elicited by transcranial magnetic stimulation over the leg representation of the primary motor cortex, maximal voluntary contractions (MVCs), and the Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 83 publications
4
45
0
Order By: Relevance
“…Recent work in spinal cord injury survivors suggests that high spasticity is associated with limited residual corticospinal connections and enhanced reticulospinal output below the lesion 36 , 37 ; this accords with clinical experience associating spasticity with the RST. 38 Against this background, it might be thought that our intervention, which aimed to strengthen reticulospinal outputs, could have risked increasing spasticity.…”
Section: Discussionsupporting
confidence: 60%
“…Recent work in spinal cord injury survivors suggests that high spasticity is associated with limited residual corticospinal connections and enhanced reticulospinal output below the lesion 36 , 37 ; this accords with clinical experience associating spasticity with the RST. 38 Against this background, it might be thought that our intervention, which aimed to strengthen reticulospinal outputs, could have risked increasing spasticity.…”
Section: Discussionsupporting
confidence: 60%
“…The reduction in the MEP amplitude size was also correlated with spasticity as one of the most common signs in humans with an SCI [ 58 ]. Spasticity causes muscle spasms, and increases muscle tone, hyperreflexia, and involuntary movements.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with an incomplete SCI and spastic muscles, the contribution of the corticospinal tract was demonstrated by TMS. Results showed that smaller MEP amplitude sizes over the area of M1 were found in patients with higher spasticity compared to healthy controls and patients with low spasticity [ 58 ]. A previous study showed that a high frequency of rTMS could effectively decrease spasticity in patients with multiple sclerosis and stroke [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…A critical question is how these contributions might take place. For example, we recently showed lesser corticospinal and larger reticulospinal influences to spastic muscles in humans with SCI (Sangari and Perez, 2019), suggesting that the contributions from corticospinal and reticulospinal tracts are imbalanced when spasticity is present (Owen et al, 2017;McPherson et al, 2018;Choudhury et al, 2019). Here, we tested SCI participants who did not have spasticity in biceps or triceps to avoid the effect of this variable on our results.…”
Section: Functional Considerationsmentioning
confidence: 97%